Trees explore, creat and investigate - Warwick, Kevin; Morgan, Pau (London QED publishing, 2018)
Trees are not only one of the oldest living species on earth but they are also one of the most important. Trees are essential for life, providing us with food, oxygen and shelter. Without trees, our planet would be a very different place. Discover all you need to know about these incredible plants and their place in our world through experiments, investigations and hands-on tasks. What On Earth?: Trees takes a cross-disciplinary approach, including links to culture, history, arts and crafts, as well as the science behind each topic. Each spread encourages children to engage with the natural world through exploration, creativity and investigation
Science (plants)
1
Keywords: Trees -- Juvenile literature; Trees